Dynamic egg color mimicry. Issue 12 (24th May 2016) - Hanley, Daniel; Šulc, Michal; Brennan, Patricia L. R.; Hauber, Mark E.; Grim, Tomáš; Honza, Marcel
Abstract: Evolutionary hypotheses regarding the function of eggshell phenotypes, from solar protection through mimicry, have implicitly assumed that eggshell appearance remains static throughout the laying and incubation periods. However, recent research demonstrates that egg coloration changes over relatively short, biologically relevant timescales. Here, we provide the first evidence that such changes impact brood parasite–host eggshell color mimicry during the incubation stage. First, we use long‐term data to establish how rapidly the Acrocephalus arundinaceus Linnaeus (great reed warbler) responded to natural parasitic eggs laid by the Cuculus canorus Linnaeus (common cuckoo). Most hosts rejected parasitic eggs just prior to clutch completion, but the host response period extended well into incubation ( 10 days after clutch completion). Using reflectance spectrometry and visual modeling, we demonstrate that eggshell coloration in the great reed warbler and its brood parasite, the common cuckoo, changes rapidly, and the extent of eggshell color mimicry shifts dynamically over the host response period. Specifically, 4 days after being laid, the host should notice achromatic color changes to both cuckoo and warbler eggs, while chromatic color changes would be noticeable after 8 days. Furthermore, we demonstrate that the perceived match between host and cuckoo eggshell color worsened over the incubation period. These findings have important implications for parasite–host coevolution dynamics, because host egg discrimination may be aided by disparate temporal color changes in host and parasite eggs. Abstract : We show that the color of great reed warbler and common cuckoo eggs change rapidly, and the extent of eggshell color mimicry shifts dynamically over the incubation period. Therefore, a host's ability to discriminate a parasitic egg may be aided by these temporal color changes.